2013
DOI: 10.1371/journal.pone.0079882
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study Points out the Causal Implication of SOX9 in the Sex-Reversal Phenotype in XX Pigs

Abstract: Among farm animals, pigs are known to show XX sex-reversal. In such cases the individuals are genetically female but exhibit a hermaphroditism, or a male phenotype. While the frequency of this congenital disease is quite low (less than 1%), the economic losses are significant for pig breeders. These losses result from sterility, urogenital infections and the carcasses being downgraded because of the risk of boar taint. It has been clearly demonstrated that the SRY gene is not involved in most cases of sex-reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 47 publications
(59 reference statements)
1
20
0
Order By: Relevance
“…In other words, the association between sex reversal in pigs and the SOX9 gene was only highlighted with more than 80 affected cases, which is very surprising when compared with some 'real monogenic' recessive traits mapped by using very few affected animals (from 3 to 12, depending on the disease) [Charlier et al, 2008]. Agreeing with this supposed complexity of the mode of inheritance, no single homozygous chromosome segment could be identified among the affected piglets of the design, and numerous haplotypes seem to be linked with the XX sex reversal trait even if 3 of them were found associated at a frequency of ∼ 64% [Rousseau et al, 2013]. Two hypotheses could explain this situation: (i) the mutation is very ancient and has invaded different haplotypes, or (ii) there are different mutations of the same SOX9 locus leading to a sex reversal phenotype.…”
Section: Sex Reversal In Pigsmentioning
confidence: 92%
See 1 more Smart Citation
“…In other words, the association between sex reversal in pigs and the SOX9 gene was only highlighted with more than 80 affected cases, which is very surprising when compared with some 'real monogenic' recessive traits mapped by using very few affected animals (from 3 to 12, depending on the disease) [Charlier et al, 2008]. Agreeing with this supposed complexity of the mode of inheritance, no single homozygous chromosome segment could be identified among the affected piglets of the design, and numerous haplotypes seem to be linked with the XX sex reversal trait even if 3 of them were found associated at a frequency of ∼ 64% [Rousseau et al, 2013]. Two hypotheses could explain this situation: (i) the mutation is very ancient and has invaded different haplotypes, or (ii) there are different mutations of the same SOX9 locus leading to a sex reversal phenotype.…”
Section: Sex Reversal In Pigsmentioning
confidence: 92%
“…Thus, if XX sex reversal in pigs has a monogenic recessive mode of inheritance, the penetrance of the trait is incomplete (i.e., some cases remain as normal females even with a homozygous mutated genotype). Interestingly, more than 10 years later and thanks to the development of a commercial porcine high throughput SNP60 BeadChip, XX sex reversal in pigs was mapped on porcine chromosome 12 to the SOX9 locus [Rousseau et al, 2013]. In this recent study, familial cases from the INRA's study have been genotyped with other 26 half/full-sib families collected between 2006 and 2010 from the Large-White population of some French breeding companies.…”
Section: Sex Reversal In Pigsmentioning
confidence: 99%
“…Moreover, an extensive genome‐wide association study (GWAS) of XX DSD pigs revealed that the candidate region harbors the SOX9 gene (Rousseau et al . ). These findings clearly indicate that searching for the causative mutation in the SOX9 region, especially in its upstream sequence, is justified.…”
Section: Introductionmentioning
confidence: 97%
“…; Rousseau et al . ), but in some human cases of this disorder, an autosomal dominant sex‐limited model, associated with duplication of the regulatory sequence upstream from SOX9 gene, was described (Cox et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the inactivation of SOX9 is responsible for XY ( SRY -positive) DSD [Foster et al, 1994]. Finally, despite the fact the causal mutation is still unknown, alterations at the SOX9 locus have been linked to XX ( SRY -negative) DSD in pigs [Rousseau et al, 2013].…”
mentioning
confidence: 99%